Public environmental supervision, environmental non-governmental organizations, and industrial green and low-carbon transformation - Zhang, Haitao; Dong, Jingrong; Zhang, Wenqing; Luo, Jiahui (Frontiers in Environmental Science, 2023)
The existing literature on China’s industrial green and low-carbon transformation primarily concerns the government’s top-down formal environmental regulation. A few studies have systematically investigated the role of informal environmental regulation represented by public environmental supervision and environmental non-governmental organizations The impact of public environmental supervision and ENGOs on industrial green and low-carbon transformation and its mechanism is empirically examined in this paper using a system GMM model and provincial panel data from 2005 to 2018. According to the findings, both Public environmental supervision and ENGOs can achieve green and low-carbon industrial transformation by promoting green technology progress; Public environmental supervision cannot collaborate with ENGOs to promote green and low-carbon industrial transformation based on national data. Further analysis indicates that the effect of public environmental supervision and ENGOs on industrial green and low-carbon transformation has significant regional heterogeneity. Public environmental supervision has a positive impact on industrial green and low-carbon transformation in the eastern and central regions. It has a negative impact on industrial green and low-carbon transformation in the western region. ENGOs promote green and low-carbon industrial transformation in the eastern and western regions. Only the eastern region has a synergistic effect on industrial greening and low-carbon transformation.